Preparation method of dry-method membrane electrode and prepared dry-method membrane electrode
Through the dry membrane electrode preparation method, electrostatic spraying and hot rolling technology are used to form a uniform catalytic layer, which solves the problems of low catalyst utilization and disordered three-phase interfaces in the prior art, and improves the performance and production efficiency of fuel cells.
Patent Information
- Application Number
- CN202411890611.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing fuel cell membrane electrode preparation methods, the catalyst utilization rate is low and the three-phase interface is disordered, resulting in limited battery performance and low swelling and production efficiency in the spraying process.
By using the dry film electrode preparation method, a uniform catalytic layer is formed by dispersing the carbon support powder and the perfluorosulfonic acid resin solution, adding platinum black powder to grinding, followed by electrostatic spraying and heat rolling treatment.
It effectively improves the utilization rate of the catalyst, improves the uniformity of the catalytic layer and the proton conduction ability, reduces the anode transmission resistance, and solves the problems of swelling and low production efficiency.
Smart Images

Figure CN119725567A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method for preparing a dry membrane electrode and the prepared dry membrane electrode. Background Art
[0002] Proton exchange membrane fuel cells are energy conversion devices that convert chemical energy in fuel and oxygen into electrical energy through electrochemical redox reactions. They have the advantages of fast response, low operating temperature, and green and pollution-free, and have become a hot spot in the technical research and development of new generation energy devices. To promote the commercialization of fuel cells, it is necessary to continuously reduce the amount of catalyst used in the membrane electrode, thereby reducing the overall manufacturing cost of the stack. However, in low-platinum or ultra-low-platinum membrane electrodes, the mass transfer problem becomes more and more serious and becomes an important factor affecting the power density of the battery.
[0003] The cathode catalyst layer of the membrane electrode is generally composed of a carbon-supported platinum catalyst and an ion resin. The ion resin conducts protons and oxygen, and the carbon carrier conducts electrons, and the reaction occurs at the three-phase interface. The catalyst slurry and the ion resin are stacked and entangled with each other irregularly, making the pore structure inside the catalyst layer very complex, which seriously limits the battery performance under high current. The preparation process of the catalyst includes two methods: transfer method and direct spraying method. The transfer method is to first spray / print the catalyst slurry onto an intermediate medium, and then transfer it to the proton exchange membrane by heating and pressurizing. This process is relatively cumbersome, and the three-phase interface of the catalyst layer formed is disordered, which affects the battery performance. Another preparation method is the direct spraying method, that is, spraying the slurry directly onto the proton exchange membrane to prepare the membrane electrode. This preparation method is simpler than the transfer method, but the splashing of the slurry during the spraying process is easy to cause waste, and in order to reduce the influence of swelling, a vacuum adsorption method is used, the production efficiency is low, and the three-phase interface of the catalyst layer formed is still disordered, which easily leads to a reduction in catalyst utilization.
[0004] Therefore, how to design a spraying process that can achieve efficient utilization of catalyst slurry and control the structure of the catalytic layer is of great significance for the development of catalytic membrane-type membrane electrode. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing a dry membrane electrode and the prepared dry membrane electrode.
[0006] In order to achieve the purpose of the invention, the technical solution adopted is as follows:
[0007] A method for preparing a dry membrane electrode comprises the following steps:
[0008] (1) dispersing the carbon support powder in water, and then adding the perfluorosulfonic acid resin solution to disperse it again;
[0009] (2) drying the dispersion obtained in step (1), adding platinum black powder, mixing, and grinding to obtain a powder mixture;
[0010] (3) The powder mixture is electrostatically sprayed onto the surface of the proton exchange membrane and hot rolled to obtain the membrane.
[0011] Preferably, the carbon carrier powder is selected from commercially available conventional models such as Vulcan XC-72, and the platinum black powder also includes but is not limited to Hispec-1000.
[0012] Preferably, the ion equivalent of the perfluorosulfonic acid resin solution is 600-1200, and the solid content is 5-25%, preferably 25%.
[0013] The perfluorosulfonic acid resin solution is an aqueous solution of perfluorosulfonic acid resin, such as Nafion solution.
[0014] Preferably, the mass ratio of the carbon carrier powder to the perfluorosulfonic acid resin solid in the perfluorosulfonic acid resin solution in step (1) is 70:30-50;
[0015] Preferably, the mass ratio of the carbon carrier powder in step (1) to the platinum black powder in step (2) is 60:40-60.
[0016] Preferably, in step (1), dispersion or redispersion is performed by ultrasound or mechanical stirring.
[0017] Preferably, the drying temperature in step (2) is 60-80° C., and the drying time is 10-24 h.
[0018] Preferably, the grinding temperature in step (2) is -30°C to -196°C, and the particle size of the powder mixture is 200nm-500nm.
[0019] Preferably, the pressure of the hot roller pressing in step (3) is 0.2-0.5 MPa, and the temperature of the hot roller pressing is 80-150°C.
[0020] The second object of the present invention is to provide a dry membrane electrode prepared by the above preparation method.
[0021] Preferably, the dry membrane electrode comprises an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane;
[0022] Preferably, the raw materials of the anode catalyst layer and the cathode catalyst layer both include carbon carrier, platinum black powder and perfluorosulfonic acid resin.
[0023] Preferably, the thickness of the anode catalyst is 1-2 μm, and the platinum loading is 0.04-0.1 mg / cm 2; The thickness of the cathode catalyst is 10-12um, and the platinum loading is 0.2-0.4mg / cm 2 .
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The manufacturing method of the present invention effectively avoids the swelling and deformation of the membrane when it encounters a solvent; and effectively avoids the agglomeration phenomenon caused by the hydrophilicity and high self-adhesiveness of the perfluorosulfonic acid resin powder.
[0026] (2) The preparation method of the present invention can effectively improve the coating of the catalyst by the perfluorosulfonic acid resin, effectively improve proton conduction, and reduce the anode transmission resistance.
[0027] (3) The dry membrane electrode preparation method of the present invention uniformly deposits the catalyst and perfluorosulfonic acid resin powder on the surface of the proton exchange membrane, improves the utilization rate of the catalyst through the electrostatic adsorption effect and the heat treatment and rolling effect of the hot pressing roller, eliminates the swelling of the proton membrane during the direct coating process, and improves the uniformity of the catalyst layer. The problem of proton membrane swelling affecting the uniformity of the membrane electrode and the product qualification rate during the direct coating process of the fuel cell membrane electrode is solved, and the problem of avoiding the uneven distribution and agglomeration of particles in the conventional dry electrode dispersion process, resulting in a reduction in the active catalytic surface area of the electrode reaction interface, and avoiding the large particles (e.g., 5-50μm) or agglomerates of perfluorosulfonic acid resin, thereby adsorbing many active catalytic sites, resulting in uneven porosity and loss of active area utilization is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The IV performance curves of the membrane electrodes prepared in Examples 1-3 and Comparative Examples 1-5;
[0029] Figure 2 This is the membrane electrode surface result image of Example 1 (SEM 300000x);
[0030] Figure 3 The surface result of the membrane electrode of Comparative Example 1 (SEM 10000x);
[0031] Figure 4 The surface result of the membrane electrode of Comparative Example 2 (SEM 2000x);
[0032] Figure 5 This is the membrane electrode surface result image of comparative example 3 (SEM10000x). DETAILED DESCRIPTION
[0033] The technical scheme in the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Although the representative embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and changes can be made to the present invention without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the embodiments, but should be limited by the attached claims and their equivalents.
[0034] Example 1
[0035] A method for preparing a dry membrane electrode, the steps are as follows:
[0036] (1) The carbon carrier powder is dispersed in deionized water by stirring, and then the perfluorosulfonic acid resin solution is added dropwise, and mechanical stirring is continued to obtain a slurry after secondary dispersion; the solid content of the entire slurry system is 10%;
[0037] The mass ratio of the carbon carrier powder to the perfluorosulfonic acid resin solid is 70:30; the model of the carbon carrier is VulcanXC-72, and the manufacturer is Cabot; the perfluorosulfonic acid resin solution is a commercial resin with an ion equivalent of 800, and the solid content of the perfluorosulfonic acid resin solution is 25%.
[0038] (2) The dispersed slurry was placed in a blast drying oven for drying at 70°C for 10 hours to obtain a solid block of the mixture; platinum black powder (model: Hispec-1000) was added to the obtained solid block of the mixture, and then cryogenically ground at -100°C for 100 minutes to obtain a ground solid powder mixture, wherein the mass ratio of the carbon carrier powder to the platinum black powder was 60:40;
[0039] (3) The obtained solid powder mixture is sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot rolled to obtain the mixture. The hot rolling pressure is 0.3 MPa and the hot rolling temperature is 100° C.
[0040] The coating thickness of the anode catalyst and cathode catalyst of the dry membrane electrode prepared by the present invention and the platinum loading can be adjusted according to actual needs. The anode catalyst coating thickness is 1-2um and the platinum loading is 0.04-0.1mg / cm 2 ; The cathode catalyst coating thickness is 10-12um, and the platinum loading is 0.2-0.4mg / cm 2 .
[0041] The platinum loading of the anode catalyst in this example is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0042] Example 2
[0043] A method for preparing a dry membrane electrode, the steps are as follows:
[0044] (1) The carbon carrier powder is dispersed in deionized water by ultrasound, and then the perfluorosulfonic acid resin solution is added dropwise, and ultrasonic stirring is continued to obtain a slurry after secondary dispersion; the solid content of the entire slurry system is 10%;
[0045] The mass ratio of carbon carrier powder to perfluorosulfonic acid resin solid is 70:50; the model of the carbon carrier is VulcanXC-72; the perfluorosulfonic acid resin solution is a commercial resin with an ion equivalent of 1000, and the solid content of the perfluorosulfonic acid resin solution is 5%.
[0046] (2) placing the dispersed slurry in a blast drying oven and drying it at 60°C for 24 hours to obtain a solid block of the mixture; adding platinum black powder to the obtained solid block of the mixture, and then performing cryogenic grinding at -196°C for 100 minutes to obtain a ground solid powder mixture, wherein the mass ratio of the carbon carrier powder to the platinum black powder is 60:60;
[0047] (3) The obtained solid powder mixture is sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot rolled to obtain the mixture. The hot rolling pressure is 0.2 MPa and the hot rolling temperature is 150° C.
[0048] The coating thickness of the anode catalyst and cathode catalyst of the dry membrane electrode prepared by the present invention and the platinum loading can be adjusted according to actual needs. The anode catalyst coating thickness is 1-2um and the platinum loading is 0.04-0.1mg / cm 2 ; The cathode catalyst coating thickness is 10-12um, and the platinum loading is 0.2-0.4mg / cm 2 .
[0049] The platinum loading of the anode catalyst in this example is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0050] Example 3
[0051] A method for preparing a dry membrane electrode, the steps are as follows:
[0052] (1) The carbon carrier powder is dispersed in deionized water by ultrasound, and then the perfluorosulfonic acid resin solution is added dropwise, and ultrasonic stirring is continued to obtain a slurry after secondary dispersion; the solid content of the entire slurry system is 10%;
[0053] The mass ratio of carbon carrier powder to perfluorosulfonic acid resin solid is 70:40; the model of the carbon carrier is VulcanXC-72; the perfluorosulfonic acid resin solution is a commercial resin with an ion equivalent of 1200, and the solid content of the perfluorosulfonic acid resin solution is 25%.
[0054] (2) placing the dispersed slurry in a blast drying oven and drying it at 80°C for 15 hours to obtain a solid block of the mixture; adding platinum black powder to the obtained solid block of the mixture, and then performing cryogenic grinding at -30°C for 100 minutes to obtain a ground solid powder mixture, wherein the mass ratio of the carbon carrier powder to the platinum black powder is 60:50;
[0055] (3) The obtained solid powder mixture is sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot rolled to obtain the mixture. The hot rolling pressure is 0.5 MPa and the hot rolling temperature is 80° C.
[0056] The coating thickness of the anode catalyst and cathode catalyst of the dry membrane electrode prepared by the present invention and the platinum loading can be adjusted according to actual needs. The anode catalyst coating thickness is 1-2um and the platinum loading is 0.04-0.1mg / cm 2 ; The cathode catalyst coating thickness is 10-12um, and the platinum loading is 0.2-0.4mg / cm 2 .
[0057] The platinum loading of the anode catalyst in this example is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0058] Comparative Example 1
[0059] The preparation method of the membrane electrode of this comparative example comprises the following steps:
[0060] (1) First, Pt / C catalyst, deionized water, perfluorosulfonic acid resin solution, and n-propanol are added to a stirring tank in sequence; the slurry is ball-milled for 12 hours at a speed of 300 rpm to obtain an anode catalyst slurry; the solid content of the slurry is 10%;
[0061] Among them, Pt / C catalyst (carbon-based nano-platinum catalyst), manufacturer Jiping, model Pt / C-SL, in which the mass fraction of platinum is 49%;
[0062] The perfluorosulfonic acid resin solution is a commercial resin with an ion equivalent of 800, wherein the mass ratio of the perfluorosulfonic acid resin solid to the catalyst is 1:2; the mass ratio of water to n-propanol in the anode catalyst slurry is 1:3;
[0063] (2) Pt / C catalyst, deionized water, perfluorosulfonic acid resin solution, and n-propanol were added to a stirring tank in sequence; the slurry was dispersed by ball milling for 12 hours at a speed of 300 rpm to obtain a cathode catalyst slurry; the solid content of the cathode catalyst slurry was 8%;
[0064] The mass fraction of platinum in the Pt / C catalyst is 45%; the perfluorosulfonic acid resin solution is a commercial resin with an ion equivalent of 800, wherein the mass ratio of the perfluorosulfonic acid resin solid to the catalyst is 1:2; the mass ratio of water to n-propanol in the cathode catalyst slurry is 1:3;
[0065] (3) The cathode and anode slurries are coated on the substrate to obtain a cathode coating and an anode coating respectively; the loading of the cathode coating is 0.3 mg / cm 2 The loading of the anode coating is 0.6 mg / cm 2 ; The substrate is a PTFE film with a thickness of 100um;
[0066] (4) The anode and cathode coatings and the proton membrane are thermally transferred to obtain the CCM membrane electrode.
[0067] The platinum loading of the anode catalyst is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0068] Comparative Example 2
[0069] The preparation method of the membrane electrode of this comparative example comprises the following steps:
[0070] (1) firstly adding catalyst powder and perfluorosulfonic acid resin powder into a stirring tank in sequence to obtain a mixed powder; ball milling the mixed powder for 12 hours at a temperature of -100° C., a time of 100 minutes, and a rotation speed of 300 rpm to obtain the anode catalyst mixed powder and the cathode catalyst mixed powder;
[0071] The catalyst is a Pt / C catalyst, in which the mass fraction of platinum is 45%;
[0072] The perfluorosulfonic acid resin powder is a commercial resin with an ion equivalent of 800 and a particle size D50 = 5 μm;
[0073] The mass ratio of perfluorosulfonic acid resin to catalyst is 1:2;
[0074] (2) The cathode catalyst mixed powder and the anode catalyst mixed powder are sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot pressed to obtain the CCM membrane electrode.
[0075] The platinum loading of the anode catalyst is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm2 .
[0076] Comparative Example 3
[0077] The preparation method of the membrane electrode of this comparative example comprises the following steps:
[0078] (1) First, Pt / C catalyst, deionized water, perfluorosulfonic acid resin solution, and n-propanol are added to a stirring tank in sequence; the slurry is ball-milled for 12 hours at a speed of 300 rpm to obtain the catalyst slurry; the solid content of the slurry is 10%;
[0079] The model of the Pt / C catalyst is Umicore 3:1 alloy; the perfluorosulfonic acid resin solution is a commercial resin with an ion equivalent of 800 and a solid content of 25%. The mass ratio of the perfluorosulfonic acid resin to the Pt / C catalyst is 1:2, and the mass ratio of water to n-propanol is 1:3.
[0080] (2) drying the catalyst slurry at 80° C. for 12 h to obtain a slurry powder block; the slurry powder block has a moisture content of <1.5%; grinding the obtained slurry powder block at low temperature at a temperature of -100° C. for 100 min to obtain a catalyst mixed powder; the catalyst mixed powder has a particle size of 400 nm;
[0081] (3) The obtained solid catalyst mixed powder is sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot rolled to obtain the mixture. The hot rolling pressure is 0.3 MPa and the hot rolling temperature is 100°C.
[0082] The platinum loading of the anode catalyst is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 1 is that the carbon carrier and the platinum black powder are mixed simultaneously to prepare the slurry.
[0085] A method for preparing a dry membrane electrode, the steps are as follows:
[0086] (1) The carbon carrier and the platinum black powder are dispersed in deionized water by stirring, and then the perfluorosulfonic acid resin solution is added dropwise, and the slurry after secondary dispersion is obtained by mechanical stirring; the mass ratio of the carbon carrier and the perfluorosulfonic acid resin solid is 70:30; the mass ratio of the carbon carrier powder and the platinum black powder is 60:50;
[0087] (2) placing the dispersed slurry in a blast drying oven and drying it at 70°C for 10 hours to obtain a solid mixture; adding platinum black powder to the obtained solid mixture, and then performing cryogenic grinding at -100°C for 100 minutes to obtain a ground solid powder mixture;
[0088] (3) The obtained solid powder mixture is sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot rolled to obtain the mixture. The hot rolling pressure is 0.3 MPa and the hot rolling temperature is 100° C.
[0089] The platinum loading of the anode catalyst is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0090] Comparative Example 5
[0091] The difference between this comparative example and Example 1 is that the temperature of low-temperature grinding is not within the optimal protection range of the present invention, specifically -15°C, and the grinding time is 100 min.
[0092] A method for preparing a dry membrane electrode, the steps are as follows:
[0093] (1) The carbon carrier and the platinum black powder are dispersed in deionized water by stirring, and then the perfluorosulfonic acid resin solution is added dropwise, and the slurry after secondary dispersion is obtained by mechanical stirring; the mass ratio of the carbon carrier and the perfluorosulfonic acid resin solid is 70:30; the mass ratio of the carbon carrier powder and the platinum black powder is 60:50;
[0094] (2) placing the dispersed slurry in a blast drying oven and drying it at 70°C for 10 hours to obtain a solid mixture; adding platinum black powder to the obtained solid mixture, and then performing cryogenic grinding at -15°C for 100 minutes to obtain a ground solid powder mixture;
[0095] (3) The obtained solid powder mixture is sprayed onto both sides of the proton exchange membrane by electrostatic spraying, and then hot rolled to obtain the mixture. The hot rolling pressure is 0.3 MPa and the hot rolling temperature is 100° C.
[0096] The platinum loading of the anode catalyst is 0.04 mg / cm 2 ; Platinum loading of cathode catalyst 0.3 mg / cm 2 .
[0097] The membrane electrodes prepared in the above embodiments and comparative examples were assembled with upper frames and gas diffusion layers on both sides to obtain a seven-in-one membrane electrode, and the IV performance curve of the membrane electrode was tested by an electrochemical test method. Figure 1 .
[0098] Depend on Figure 1 It can be seen that the seven-in-one membrane electrode prepared by the dry membrane electrode prepared by Examples 1-3 of the present invention has an increased working voltage, increased power, and better performance than other membrane electrodes at the same current density. Comparative Example 1 uses a transfer method to prepare a membrane electrode, Comparative Example 2 uses a mixture of two powders of a Pt / C catalyst and a perfluorosulfonic acid resin to prepare a membrane electrode, Comparative Example 3 uses a Pt / C catalyst powder directly mixed with a perfluorosulfonic acid resin solution to prepare a membrane electrode, and Comparative Example 4 uses a carbon carrier and a platinum black powder to mix and prepare a slurry; Comparative Example 5 uses an inappropriate low-temperature grinding process, and the seven-in-one membrane electrode finally obtained, compared with the membrane electrode of the present invention, has a different degree of decrease in working voltage and power at the same density, and the performance is not as good as the present invention.
[0099] The prepared membrane electrode was observed under a microscope. The surface results of the membrane electrode of Example 1 are shown in FIG. Figure 2 The membrane electrode surface results of Comparative Example 1 are shown in Figure 3 The membrane electrode surface results of Comparative Example 2 are shown in Figure 4 The membrane electrode surface results of comparative example 3 are shown in Figure 5 The results show that Example 1 of the present invention can effectively improve the coating of the catalyst by the perfluorosulfonic acid resin, thereby effectively improving proton conduction and reducing the anode transmission resistance, compared with Comparative Examples 1-3.
[0100] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a dry membrane electrode, characterized in that: The steps include: (1) dispersing the carbon support powder in water, and then adding the perfluorosulfonic acid resin solution to disperse it again; (2) drying the dispersion obtained in step (1), adding platinum black powder, mixing, and grinding to obtain a powder mixture; (3) The powder mixture is electrostatically sprayed on both sides of the proton exchange membrane and hot rolled to obtain the membrane.
2. The preparation method according to claim 1, characterized in that: The ion equivalent of the perfluorosulfonic acid resin solution is 600-1200, and the solid content is 5-25%.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon carrier powder to the perfluorosulfonic acid resin solid in the perfluorosulfonic acid resin solution in step (1) is 70:30-50.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon carrier powder in step (1) to the platinum black powder in step (2) is 60:40-60.
5. The preparation method according to claim 1, characterized in that: In step (1), dispersion or redispersion is performed by ultrasound or mechanical stirring.
6. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 60-80° C. and the drying time is 10-24 hours.
7. The preparation method according to claim 1, characterized in that: The grinding temperature in step (2) is -30°C to -196°C, and the particle size of the powder mixture is 200nm-500nm.
8. The preparation method according to claim 1, characterized in that: The pressure of the hot roller pressing in step (3) is 0.2-0.5 MPa, and the temperature of the hot roller pressing is 80-150°C.
9. A dry membrane electrode prepared by the preparation method according to any one of claims 1 to 8.
10. The dry membrane electrode according to claim 9, characterized in that: The anode catalyst coating thickness of the dry membrane electrode is 1-2 um, and the platinum loading is 0.04-0.1 mg / cm 2 ; Cathode catalyst coating thickness 10-12um, platinum loading 0.2-0.4mg / cm 2 .
Citation Information
Cited By
Dry-method membrane electrode of fuel cell and preparation method of dry-method membrane electrode
CN120878855A
Catalytic layer with controllable ionomer catalyst interface and preparation method thereof
CN121097100A
Platinum-doped proton exchange membrane, preparation method thereof and fuel cell
CN121662882A